Health Informatics for Development: a Threepronged Strategy of Partnerships, Standards, and Mobile Health - Marcelo, A.; Adejumo, A.; Luna, D. (Yearbook of Medical Informatics, 2011)
Describe the issues surrounding health informatics in developing countries and the challenges faced by practitioners in building internal capacity. From these issues, the authors propose cost-effective strategies that can fast track health informatics development in these low to medium income countries (LMICs).The authors conducted a review of literature and consulted key opinion leaders who have experience with health informatics implementations around the world.Despite geographic and cultural differences, many LMICs share similar challenges and opportunities in developing health informatics.Partnerships, standards, and inter-operability are well known components of successful informatics programs. Establishing partnerships can be comprised of formal inter-institutional collaborations on training and research, collaborative open source software development, and effective use of social networking. Lacking legacy systems, LMICs can discuss standards and inter-operability more openly and have greater potential for success. Lastly, since cellphones are pervasive in developing countries, they can be leveraged as access points for delivering and documenting health services in remote under-served areas. Mobile health or mHealth gives LMICs a unique opportunity to leapfrog through most issues that have plagued health informaticsin developed countries. By employing this proposed roadmap, LMICs can now develop capacity for health informaticsusing appropriate and cost-effective technologies.
Keywords: eHealth; mHealth; mobile; partnerships; information systems